Family Attitudes and Behavior toward Tuberculosis Prevention in the Lembang Health Center Area, West Sulawesi, Indonesia - Muzakkir, Muzakkir; Husaeni, Hermin; Muzdaliah, Ika; Annisa, Nurul (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: People mostly have the perception that tuberculosis is an unexpected disease to occur because it greatly hinders family development. The existence of this disease tends to break social interaction. This perception will affect the attitudes and behavior of those who will prevent this disease from occurring in their families and environment. AIM: This study aimed to determine the correlation between family attitudes and behavior with efforts to prevent infectious tuberculosis disease in the work area of Lembang Public Health, Majene, West Sulawesi. METHODS: This quantitative research was conducted through a cross-sectional approach. Based on total sampling, as many as 31 respondents who were part of families with tuberculosis were involved as samples. RESULTS: The bivariate analysis with the Chi-square test showed that the correlation between attitudes and TB prevention had a p = 0.301 (⍺ = 0.05). Then, the correlation of behavior with TB prevention had a p = 0.413 (⍺ = 0.05). CONCLUSION: Thus, no significant correlation was identified between family attitudes and behavior toward tuberculosis prevention.